Effects of Dietary Lipid Sources on Alleviating the Negative Impacts Induced by the Fishmeal Replacement With Clostridium autoethanogenum Protein in the Diet of Pacific White Shrimp (Litopenaeus vannamei) - Zheng, Chaozhong; Gong, Shunlian; Cao, Junming; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Tan, Beiping (Frontiers in Marine Science, 2022)
This study evaluated the effects of lipid sources on the replacement of fishmeal with Clostridium autoethanogenum protein (CAP) in the diet of Pacific white shrimp (Litopenaeus vannamei). By using CAP to replace 40% fishmeal in the basal diet (contains 25% fishmeal), four diets (PC as the control diet, LSO as the low soybean oil level, MSO as the middle soybean oil level and HSO as the high soybean oil level) were formulated by adding different proportions of fish oil and soybean oil. Each diet was assigned to four replicates (40 shrimps per replicate, initial weight = 1.79 ± 0.02 g). A 7-day Vibrio parahaemolyticus challenge test was conducted at the end of the 50-day feeding experiment. Weight gain was significantly higher and the cumulative mortality after challenge was lower in HSO treatment. The total antioxidant capacity (T-AOC) in hepatopancreas was significantly raised with increasing dietary soybean oil based on CAP substitution. After challenge, Pen3 mRNA expression was significantly higher in hepatopancreas and NF-κB pathway related mRNA (dorsal, relish and IKKβ) expression was higher in intestine in HSO treatment. The height of mucosal folds and thickness of the muscle layer were positively correlated with the level of dietary soybean oil. Transmission electron microscopy (TEM) analysis showed that the microvilli were damaged and the endoplasmic reticulum was swollen in shrimp fed LSO diet. Diversity of intestinal microbiota was increased in shrimp fed LSO diet, with a significantly increase in beneficial bacteria such as Halocynthiibacter and Ruegeria as well as less harmful bacteria such as Vibrio. These results suggested that the replacement of fishmeal with CAP and the high proportion of soybean oil in the diet could improve the growth performance and disease resistance and intestinal structure of Pacific white shrimp, and high fish oil in low FM diet raised the percentage of beneficial bacteria in intestinal of shrimp.